Pseudoaneurysm formation after valve sparing root replacement in children with Loeys‐Dietz syndrome. Issue 6 (3rd May 2018) - Liu, Rui H.; Fraser, Charles D.; Zhou, Xun; Cameron, Duke E.; Vricella, Luca A.; Hibino, Narutoshi
Abstract: Background: Loeys‐Dietz syndrome (LDS) is an autosomal dominant connective tissue disorder predisposing patients to aneurysm formation and arterial dissection. Aortic root replacement is often performed prophylactically and valve‐sparing root replacement (VSRR) has become the procedure of choice. However, in these patients with connective tissue disorders, postoperative pseudoaneurysms may develop. Methods: All children with LDS undergoing VSRR at a single institution were retrospectively reviewed to identify patients who developed postoperative pseudoaneurysms. Results: Thirty‐one children with LDS underwent VSRR; four of these developed pseudoaneurysms of their synthetic aortic root grafts requiring reoperation. These four children were reviewed to investigate the cause of pseudoaneurysm formation after VSRR. Each had severe subtypes of LDS. Each underwent reoperation for repair of their pseudoaneurysms and were found to have suffered pseudoaneurysms as a result of tearing of sutures from their reimplantation VSRR. Conclusions: Pseudoaneurysms following aortic root replacement with VSRR can occur in children with severe subtypes of LDS. Long‐term surveillance is required to detect these potentially life‐threatening lesions.